PENGARUH PENGUNAAN MEDIA MANIK-MANIK DALAM TATANAN PENDEKATAN MATEMATIKA REALISTIK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II SDN 034 TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Jesi Alexander Alim; Jalinus; Purnama Sari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2014)
The mathematics learning process implemented by teachers in grade II of SDN 034 Tarai Bangun had not yet employed engaging instructional methods, resulting in passive student participation. Learning activities were predominantly teacher-centered, with an emphasis on explaining mathematical theory without involving students in discovering concepts through real and meaningful activities. This condition limited students’ conceptual understanding and learning outcomes. This research aimed to determine whether the use of bead media within the Realistic Mathematics Education (RME) approach could improve students’ mathematics learning outcomes in class II.A of SDN 034 Tarai Bangun in the 2013/2014 academic year. The research involved 26 students and applied an experimental design consisting of an experimental class and a control class. Based on the analysis of pretest and posttest data, learning outcomes increased in both classes, although the improvement in the experimental class was significantly higher. In the experimental class, the average pretest score increased from 60.95 to 75.42, showing an improvement of 23%. Meanwhile, in the control class, the average score increased from 55.16 to 58.06, with an improvement of only 5%. These results indicate that the integration of bead media through the Realistic Mathematics Education approach was more effective in enhancing students’ learning outcomes. To examine whether the difference between the two classes was statistically significant, a t-test was conducted with 60 degrees of freedom. The results showed that the calculated t-value was greater than the critical value of the t-table, leading to the rejection of the null hypothesis (H₀) and acceptance of the alternative hypothesis (H₁). Therefore, it can be concluded that there was a significant difference in mathematics learning outcomes between students taught using bead media within the RME approach and those taught using conventional methods.